PENGARUH PSIKOLOGIS KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN LAPTOP ASUS DI KOTA BIMA - FARHAN FARHAN; KARTIN APRIANTI (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2022)
The purpose of this study was to determine whether there is a consumer's psychological influence on the purchasing decision of Asus laptops in Bima City. The population used in this study were all unknown consumers of Asus laptop users in Bima City. The sampling technique in this study used Quota Sampling, which is a sampling technique from a population that has certain characteristics to the desired amount. The sample in this study were 90 respondents. The sampling technique used incidental sampling. The results showed that consumer psychology had a positive and significant effect on purchasing decisions at Asus leptops in Bima City. Consumer psychology influenced the purchasing decision of Asus leptop in Bima City by 25.8%.